The Learned and the Common People. Two Traditions in the Latvian Mythology - Pūtelis, Aldis (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
The present article follows the formation of a view on the Latvian mythology, distinctly different from the one that can be drawn from the analysis of the folklore texts. It can be concluded that the cause for this discrepancy is the attitude of the learned men authoring the different texts describing the mythology of the local people in more or less detail. They relied basically on writings of other authors instead of the living tradition itself, as any folkloristic or anthropological approach was yet the matter of far future. By repeating the data found in other written works, this information appears to be widely known and completely reliable. The ultimate collection of all the data is to be found in an appendix to the “Latvian Grammar” by Gotthard Friedrich Stender – an outstanding representative of Enlightenment in Latvia. In order to trace the development of the particular corpus of data included in this work, the probable earlier sources are analysed, comparing the available data to establish their relations.